The Association Between BXO and Obesity in Boys Undergoing Circumcision. (22nd November 2017) - Fuchs, Molly E.; Beecroft, Nicholas; Dajusta, Daniel G.; McLeod, Daryl J.
This study investigated whether boys with balanitis xerotica obliterans (BXO) have increased rates of obesity compared with boys with no concern for BXO (NCB). Boys ≤18 years old with circumcision pathology–confirmed BXO were compared with an age-matched group who had NCB during circumcision. Boys with BXO were found to have a mean body mass index of 70.64 percentile for age compared with 52.43 percentile in age-matched controls ( P = .0005). The rate of obesity was significantly higher in boys with BXO (42%) compared with 12.4% in boys with NCB (odds ratio = 5.12; 95% CI = 2.6 to 10.06). Given the increasing rates of childhood obesity and the long-term health consequences of both BXO and obesity, special attention should be paid to this population. Further research is needed to determine if BXO in obese children may represent an early indicator of a systemic disease process where intervention may be warranted.